FOREIGN AID DECREASE – THREAT FOR MILLENNIUM DEVELOPMENT GOLAS? - Klaudia Lindtnerova (European Scientific Journal, ESJ, 2014)
This paper investigates the relationship between foreign aid and growth in real GDP per capita in Africa in the period 1980 – 2012 using regression. It examines whether foreign aid flows have any effect on the effectiveness of foreign aid and Millennium Development Goals. The results show that the effect of aid on economic growth in Africa is not significant. The paper concludes that the quantity of foreign aid flows is not a significant determinant of GDP growth in Africa. The recent decrease of foreign aid flows should not poses any threat to achieving Millennium Development Goals.